A Pedagogical Architecture for Systems Design and Development in Remote Learning Based on Software Ecosystems Characteristics - Feitosa, Rodrigo; Malcher, Paulo; Viana, Davi; Santos, Rodrigo Pereira dos (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2025: Anais do XXIV Simpósio Brasileiro de Qualidade de Software, 2025)
The COVID-19 pandemic forced universities to transition to remote learning, presenting challenges for teaching programming. Thus, it is important to teach programming through new system development trends, such as software ecosystems (SECO), that consider social and technical aspects to bring students closer to the reality of the industry, even remotely. This work aims to propose and apply PA4SDD-SECO, a pedagogical architecture for systems design and development in remote learning based on SECO characteristics. PA4SDD-SECO was applied in an undergraduate information systems course, where an observational study was used to analyze the relationship of influence among students, and a questionnaire was used to analyze both PA4SDD-SECO and the relationship of influence among students according to their perceptions. As a result, PA4SDD-SECO improved student cooperation, regardless of geographic distance, and helped share experiences. We found that feedback directed at one project in SECO can influence others, even when geographically distant.